Kekuatan Pembuktian Dokumen Elektronik sebagai Alat Bukti Perluasan dalam Persidangan Perdata di Era Transformasi Digital - Susy Putri Wihadi; Alfred Ariyanto; Nunuk Jati Saputri; Thomas Mulyanto Kurniawan (Prosiding Seminar Nasional Ilmu Hukum, 2026)
The digital transformation of the Indonesian judicial system through the implementation of e-court and e-litigation necessitates a redefinition of conventional evidentiary laws, which have historically been governed by the Herziene Inlandsch Reglement (HIR) and the Rechtreglement voor de Buitengewesten (RBg). This research aims to analyze the evidentiary strength of electronic documents as expanded means of proof in civil proceedings and to identify the challenges regarding their implementation. The research method employed is normative legal research using a statutory approach and a conceptual approach. The findings indicate that based on the principle of functional equivalence, electronic documents hold a legal status equivalent to paper-based documents, provided they meet the requirements of integrity, accessibility, and authenticity through certified electronic signatures as mandated by Law Number 1 of 2024 concerning Electronic Information and Transactions. The evidentiary strength of an electronic document may reach the level of conclusive evidence, similar to an authentic deed, if supported by a reliable electronic system. However, implementation still faces technical hurdles concerning metadata verification and limited human resource competency within the judiciary. This research recommends the urgent need for a new codification of civil procedural law and the standardization of digital forensic procedures in trials to ensure legal certainty and justice for all parties in the digital era.